2017
DOI: 10.1063/1.4984725
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement and pumping power optimization using CuO-water nanofluid through rectangular corrugated pipe

Abstract: Abstract. Heat transfer enhancement by corrugation in fluid domain is a popular method. The rate of improvement is more when it is used highly thermal conductive fluid as heating or cooling medium. In this present study, heat transfer augmentation was investigated numerically by implementing corrugation in the fluid domain and nanofluid as the base fluid in the turbulent forced convection regime. Finite volume method (FVM) was applied to solve the continuity, momentum and energy equations. All the numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It was observed that the effective pumping power ratio could be accomplished by considering high viscosity nanofluids. Salehin et al [645] investigated the effect of pumping power for a rectangular corrugated pipe and noticed that the lower pumping power is required for the low concentration of…”
Section: Pumping Powermentioning
confidence: 99%
“…It was observed that the effective pumping power ratio could be accomplished by considering high viscosity nanofluids. Salehin et al [645] investigated the effect of pumping power for a rectangular corrugated pipe and noticed that the lower pumping power is required for the low concentration of…”
Section: Pumping Powermentioning
confidence: 99%
“…The results showed that at Re $Re$ = 25,000 and VR = 5%, there was 67% increase in heat transfer coefficients. Salehin et al 30 examined the effect of nanoparticle VR, italicRe ${Re}$, corrugation amplitude, and corrugation wavelength on the CHTP of CuO/H 2 O nanofluid flowing through rectangular corrugated pipes. The authors reported an increase in corrugation amplitude, VR, and italicRe ${Re}$ enhanced italicNu ${Nu}$.…”
Section: Introductionmentioning
confidence: 99%